Moral Ecosystem and Pesantren Sustainability: A Multi-Site Qualitative Study in Indonesia - Taufikin Taufikin (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study examines how the sustainability of Islamic boarding schools (pesantren) is maintained though moral practices and social relations beyond formal management systems. Using a qualitative multi-site case study across four Islamic boarding schools in Indonesia, data were collected through interviews, observations, and document analysis. The findings reveal that sustainability is shaped by moral ecosystem consisting of Kiai authority, pedagogy care, religious habituation, and parent trust. These elements interact dynamically to reproduce institutional stability and legitimacy.This study offers a novel conceptual framework as an moral ecosystem as an alternative to managerial approaches in understanding eduactional sustainability. Keywords: Kiai authority, moral ecosystem, pesantren sustainability, religious habitus, social trust.